The Influence of Work Environment and K3 (Occupational Safety and Health) on The Performance of Employees in The Production Department at PT. Subafood Pangan Jaya Cikupa, Tangerang Regency - Mutmainnah, Ummu Ghaida; Hermawati, Rahmi (International Journal of Social Sciences, 2025)
This research aims to determine the partial and simultaneous influence of the work environment, occupational safety and health on employee performance at PT. Pangan Jaya Subafood. The method used in this research is quantitative with a descriptive associative approach and saturated sampling technique with a population and sample of 164 respondents. The analytical methods used include linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and Hypothesis Testing as a means of proving the hypothesis. The correlation coefficient value of the work environment, occupational safety and health on employee performance is at the level of 0.375, so the level of correlation between variables is interpreted as low. Hypothesis testing obtained a value of Subafood Pangan Jaya, Hypothesis testing obtained a value of Pangan Jaya Subafood, The results of this research are the work environment (X1) and work safety and health (X2) with the regression equation Y = 19.256 + 0.262X1 + 0.173X2 which can be interpreted as the work environment and work safety and health having a positive effect on employee performance. Partial or simultaneous hypothesis testing obtained fcount > ftable (13.121 > 3.05) and significant < 0.05 (0.000 < 0.05), so Ho3 is rejected and Ha3 is accepted, meaning that the work environment (X1) and occupational safety and health (X2) have a positive and insignificant effect on employee performance. The results of the Determination coefficient analysis which were tested together had an influence of 0.141 or 14.1% while the remaining 85.9% was influenced by other factors.